Revisiting the interaction between complement lectin pathway protease MASP-2 and SARS-CoV-2 nucleoprotein - Bally, Isabelle; Drumont, Guillaume; Rossi, Véronique; Guseva, Serafima; Botova, Maiia; Reiser, Jean-Baptiste; Thépaut, Michel; Dergan Dylon, Sebastian; Dumestre-Pérard, Chantal; Gaboriaud, Christine; Fieschi, Franck; Blackledge, Martin; et al. (Frontiers in Immunology, 2024)
Complement activation is considered to contribute to the pathogenesis of severe SARS-CoV-2 infection, mainly by generating potent immune effector mechanisms including a strong inflammatory response. Involvement of the lectin complement pathway, a major actor of the innate immune antiviral defense, has been reported previously. It is initiated by recognition of the viral surface Spike glycoprotein by mannose-binding lectin (MBL), which induces activation of the MBL-associated protease MASP-2 and triggers the proteolytic complement cascade. A role for the viral nucleoprotein (N) has also been reported, through binding to MASP-2, leading to protease overactivation and potentiation of the lectin pathway. In the present study, we reinvestigated the interactions of the SARS-CoV-2 N protein, produced either in bacteria or secreted by mammalian cells, with full-length MASP-2 or its catalytic domain, in either active or proenzyme form. We could not confirm the interaction of the N protein with the catalytic domain of MASP-2 but observed N protein binding to proenzyme MASP-2. We did not find a role of the N protein in MBL-mediated activation of the lectin pathway. Finally, we showed that incubation of the N protein with MASP-2 results in proteolysis of the viral protein, an observation that requires further investigation to understand a potential functional significance in infected patients.